READINGS IN INDIAN SOCIOLGY VOLUME 9 : CULTURE AND SOCIETY - Visvanathan, Susan (New Delhi Sage Publications, 2014)
A 10-volume series, that presents a collection of essays on Indian sociology published over the years in the Sociological Bulletin, the oldest sociology journal in India, published by the Indian Sociological Society (ISS).
Keywords: SOCIOLOGY - INDIA -- CULTURE-INDIA -- SOCIETY-INDIA